KAJIAN PEMASARAN IKAN KERAPU (Cromileptes Altivelis Sp) DI TANJUNG LIMAU KELURAHAN BONTANG BARU KOTA BONTANG - Fitri Yuliani; Eko Sugiharto; Nurul Ovia Oktawati (Jurnal Pembangunan Perikanan dan Agribisnis, 2017)
The aim of this research were to determine marketing value, marketing channel,marketing margin and marketing efficiency of grouper based on species at Tanjung Limau, Bontang Baru sub District, Bontang Utara District, Bontang City. This Research conduct for six (10) month from Agustus 2013 to Mei 2014, At Tanjung Limau, Bontang Baru sub district, Bontang City. Data were collected using purposive sampling method to choose 13 respondents around research area. The result shown there was single pattern for marketing channels. Marketing Margin for five (5) species were Rp. 20.000,- for humpback grouper and Rp. 10.000,- for brown marble grouper, Rp. 15.000,- for estuary grouper, Rp.10.000,- for spotted coral grouper and Rp.10.000,- for humpback grouper. Marketing eficiency for five (5) species were 20% for humpback grouper 10% for brown marble grouper, 10% for estuary grouper, 20% for spotted coral grouper, and 10% for humpback grouper.